Parenting Styles and Peer Pressure in Relation to Academic Performance Among Adolescents - Salbia Abbas; Adeena Shahzad; Eman Shahid; Ayesha Basharat (Research Journal of Psychology, 2025)
The present study aimed to examine the influence of parenting styles and peer pressure on academic performance among university students. A random sample of 258 students aged 18–26 years was collected from various universities. Participants completed a self-developed demographic sheet, the Perceived Parenting Style Scale (Divya & Manikandan, 2013), and the Peer Pressure Scale Questionnaire Revised (Saini & Singh, 2016). Descriptive statistics, Pearson product-moment correlation, and regression analyses were conducted. The findings indicated a significant weak negative correlation between academic performance (measured by CGPA) and peer pressure (r = -.14, p < .05), while an insignificant negative correlation was observed between academic performance and parenting styles (r = -.016, p > .05). A significant strong positive correlation was found between peer pressure and parenting styles (r = .32, p < .01). Regression analysis revealed that peer pressure significantly predicted academic performance (ß = -.152, p < .05), whereas parenting styles did not significantly predict academic performance (ß = .032, p > .05). The model explained only 2.1% of the variance in academic performance (R² = .021, F(2, 255) = 2.754, p > .01). These findings suggest that peer pressure negatively affects academic performance, albeit weakly, while parenting styles exhibit no substantial relationship with academic performance in this sample. However, peer pressure and parenting styles are significantly correlated, indicating a potential interaction worth exploring in future research. This study highlights the need for further investigation into the complex dynamics between external influences and academic outcomes among university students.